ANALISIS EFEKTIFITAS RETRIBUSI PELAYANAN PASAR TANJUNG DAN KONTRIBUSINYA TERHADAP PENDAPATAN ASLI DAERAH KOTA MOJOKERTO (STUDI PADA DINAS PENDAPATAN PENGELOLAAN KEUANGAN DAN ASET KOTA MOJOKERTO) - Anggraini, Novita Eka (Jurnal Mahasiswa Perpajakan, 2015)
The Objective of research is to understand the effectiveness, the contribution, and the growth rate of Service Retribution of Tanjung Market on Local Genuine Income of Mojokerto City. The role of local retribution has the greatest role compared to other sources of Local Genuine Income in Mojokerto City. Service Retribution of Tanjung Market has never achieved the target in budget year of 2009-2012. Indeed, Service Retribution of Tanjung Market does not give contribution to the target, or it is still less than what has been targeted. Therefore, Local Genuine Income of Mojokerto City may be less than the excepted income. Intensification and extensification are recommended. It is also suggested that structures and infrastructures shall be improved, the counseling program must be given on the collector officer to develop transparency, and the retribution payers are encouraged to be more regular and discipline in meeting the obligation. Keywords: The Effectiveness of Service Retribution of Tanjung Market, Contribution, Growth Rate